Global Economic Policy Uncertainty and Islamic Stock Market in Indonesia - Mashilal, Mashilal; Amalia, Farah; Visita, Luksi (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The investigation of economic policy uncertainty (EPU) was necessary during financial and trade integration between countries. In this context, there was a spillover effect of global economic policy protections impacting stock markets. Therefore, this research aimed to determine the effect of global policy proxied by the United States, China, and Japan on Islamic stock market in Indonesia. Macroeconomic indicators were also included in the research model and the time series data was obtained from January 2015 to December 2022. In addition, Vector Error Correction Model (VECM) was used as an analytical method in the model. The results showed that Islamic stocks responded positively to global economic policy, exchange rates, and exports to stock index, while inflation reported a negative response.